FACTORS RELATED TO THE INCIDENCE OF ARI AT TANJUNG AGUNG HEALTH CENTER - Ramayani; Toto Harto (Majalah Kedokteran Sriwijaya, 2023)
Abstract: ARI (Upper respiratory tract infection) is 48,325 children and estimates in developing countries range from 30-70 times higher than developed countries and it is suspected that 20% of babies born in developing countries fail to reach the age of 5 years and 25-30% of child deaths are caused by ARI (Milo et al., 2021). In general, the purpose of the study is to know the factors associated with the incidence of ARI disease in children under five in the working area of the UPTD Tanjung Agung Health Center in 2022. This study included research using quantitative correlation methods with Cross Sectional approach and a sample number of 80 people. The variables studied are presented in the form of frequency distribution tables and tested by univariate and bivariate analysis, namely by using demographic data questionnaire instruments, questionnaires. The results of the chi square test get a p value of 0.000, meaning that there is a relationship between knowledge and the incidence of ARI. p value 0.000 means that there is a relationship between smoking habits and the incidence of ARI. p value of 0.037 means that there is no exclusive breastfeeding relationship with the incidence of ISPA in the UPTD Tanjung Agung Health Center Working Area in 2022. The conclusion in this study is that there is a relationship between knowledge and smoking habits with the incidence of ARI. Meanwhile, exclusive breastfeeding has nothing to do with the incidence of ARI in the UPTD Tanjung Agung health center work area in 2022.